(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The increase in development and progress develops with the speed of the technology wheel and its impact on consumer satisfaction. Reasonably the electronic retail trade has the largest share. This research provides an abundant experience on the Jordanian consumer satisfaction with E- retail trade-in particular after customs facilities. The empirical study consists of 521 questionnaires and analysing the outputs, through which the sites are evaluated on more than one side, to come out with the most important strengths and weak points of the e-retail trade. Each question in the questionnaire is evaluated and assigned a unique loading factor. Four major evaluation metrics have been adopted to investigate the customer’s thoughts on E-retail which includes Reliability, Design, Process, and safety. In addition, factor analysis of the Correlation Matrix with the samples sequence along with Goodness-of-fit indices have been carried out for the experimentation. The obtained insights from the empirical study are also validated using confirmatory factor analysis. Furthermore, to presenting problems with high rates to solve them.